From private to public to private again: a long-term perspective on nationalization - Toninelli, Pierangelo (2008)
The article summarizes the main phases of the long-term process of rise and fall of state-owned enterprise (SOE) in the Western world. It focuses first on the waves of nationalization that occurred in the last century, addressing the major motives that explained them. Next, moving from the changing environment that opened the way toward the rush to privatization of the last two decades, it dwells on the quantitative dimension of the de-nationalization phenomenon and offers some thoughts on its consequences.